2020
DOI: 10.3748/wjg.v26.i32.4763
|View full text |Cite
|
Sign up to set email alerts
|

Immune and microRNA responses toHelicobacter muridaruminfection and indole-3-carbinol during colitis

Abstract: BACKGROUND Indole-3-carbinol (I3C) and other aryl hydrocarbon receptor agonists are known to modulate the immune system and ameliorate various inflammatory and autoimmune diseases in animal models, including colitis induced by dextran sulfate sodium (DSS). MicroRNAs (miRNAs) are also gaining traction as potential therapeutic agents or diagnostic elements. Enterohepatic Helicobacter (EHH) species are associated with an increased risk of inflammatory bowel disease, but lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 94 publications
(100 reference statements)
1
3
0
Order By: Relevance
“…Tryptophan supplementation did not modify the severity of symptoms in AhR-deficient mice, confirming the dependency on AhR activation (34). Consistent with these observations, symptoms of DSSinduced colitis were mildly ameliorated when mice fed on normal chow were given tryptophan supplementation in the drinking water (37) or I3C by oral gavage (38). In mice fed on AhR ligand-free synthetic diet, increased epithelial damage may be due to the lack of IL22 production in response to DSSinduced inflammation (26,34).…”
Section: What Is the Impact Of Nutritional Ahr Ligands On Intestinal Immunity?supporting
confidence: 57%
“…Tryptophan supplementation did not modify the severity of symptoms in AhR-deficient mice, confirming the dependency on AhR activation (34). Consistent with these observations, symptoms of DSSinduced colitis were mildly ameliorated when mice fed on normal chow were given tryptophan supplementation in the drinking water (37) or I3C by oral gavage (38). In mice fed on AhR ligand-free synthetic diet, increased epithelial damage may be due to the lack of IL22 production in response to DSSinduced inflammation (26,34).…”
Section: What Is the Impact Of Nutritional Ahr Ligands On Intestinal Immunity?supporting
confidence: 57%
“…We previously published I3C, a naturally derived AhR ligand and molecule found in cruciferous vegetables, was effective at reducing disease severity in animal models of colitis [13], which was similarly reported by others [29][30][31][32][33]. In one of the earliest reports of this by Li et al, the researchers established that I3C-mediated protective effects were dependent on AhR since global knockout of AhR in mice prevented I3C from reducing disease severity in the DSS model [34].…”
Section: Discussionmentioning
confidence: 52%
“…Our lab has also previously shown that I3C attenuates staphylococcal enterotoxin B-mediated liver injury by downregulating miR-31 expression ( 64 ). I3C-mediated miRNA dysregulation was also shown in other inflammatory and cancer models ( 65 , 66 ). In the current study, we performed scRNAseq and miRNAseq to look at the dysregulated mRNAs and miRNAs in whole lungs when comparing the LPS+Veh versus LPS+I3C groups of mice.…”
Section: Discussionmentioning
confidence: 72%